2020
DOI: 10.1002/berj.3693
|View full text |Cite
|
Sign up to set email alerts
|

Legitimising populist education in Israel: The role of religion

Abstract: This article analyses two case studies from the Israeli education system that demonstrate how religious themes and language are used in service of populist politics. First, 'Being Citizens in Israel' is the standard high school civics textbook that underwent a major revision in 2015. The second case study focuses on new school programmes that focus on the rebuilding of the Third Jewish temple, and the inclusion of references to the Third Temple in other school subject curricula. Both cases were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…These authors found that the textbooks highlighted the dangers of Hong Kong's assimilation to the Chinese mainland, inculcating in readers a rejection of almost everything about China. These findings echo those of Silberberg and Agbaria (2021) regarding the heightened division between the insider group (Hong Kongers) and the outsider group (those of the Chinese mainland) from a populist viewpoint, as well as Moffit and Tormey's (2014) descriptors of the key elements of populist style: the notion of crisis (depicting China's assimilation of Hong Kong in the LST) and disseminating "bad manners" in political discourse (commending radical protests in the LST). These LST may thus be suspected of contributing to populist views.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…These authors found that the textbooks highlighted the dangers of Hong Kong's assimilation to the Chinese mainland, inculcating in readers a rejection of almost everything about China. These findings echo those of Silberberg and Agbaria (2021) regarding the heightened division between the insider group (Hong Kongers) and the outsider group (those of the Chinese mainland) from a populist viewpoint, as well as Moffit and Tormey's (2014) descriptors of the key elements of populist style: the notion of crisis (depicting China's assimilation of Hong Kong in the LST) and disseminating "bad manners" in political discourse (commending radical protests in the LST). These LST may thus be suspected of contributing to populist views.…”
Section: Introductionsupporting
confidence: 64%
“…The LST corpus analysis also revealed language discouraging the self-acknowledgement of Chinese identity, also echoing Li and Wu (2022), who asserted that LST directly called for Hong Kong people to distance their identity from that of mainland Chinese. These findings demonstrate a key feature of populism, heightened division between the inner and outer groups (Silberberg & Agbaria, 2021). Therefore, the textbooks can be understood as containing populist elements that exclude the outer group, China, from the local inner group, Hong Kong.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations